The association between death anxiety with spiritual experiences and life satisfaction in elderly people - Taghiabadi, Mina (Electron Physician, 2017)
INTRODUCTION: Death anxiety is a concept with greater importance among the elderly as they approach inevitability of death. Identifying the correlates of death anxiety among old people is important in order to reduce the burden of this problem. Therefore, the present study was performed with the aim to examine the association between spiritual experiences and life satisfaction with death anxiety in this stage of life. METHOD: This cross-sectional study with descriptive-analytical design included 190 elderly people visiting the health and medical centers of Neyshabur city, Iran, during fall and winter, 2016. Participants were asked to complete three questionnaires including a 16-item spiritual experiences scale, life satisfaction index proposed by Wood and Shifor with 13 items, and a 27-item death anxiety scale developed by Aminpour. Analytical statistics (Spearman’s correlation coefficient, Pearson’s correlation coefficient) were conducted using SPSS software version 22. RESULTS: Fifty-eight percent of participants were in younger elderly age group with mean age of 68.18±7.13 years and the number of men and women was the same (95). A significant positive association between spiritual experiences and life satisfaction (r=0.2, p<0.05), a significant negative association between spiritual experiences and death anxiety (r=−0.184, p< 0.05) and a significant negative relationship between life satisfaction and death anxiety (r=−0.2, p<0.05) was found. CONCLUSION: Based on results, it seems that reducing stressors in this stage of life including reduction of death anxiety, is possible through use of spiritual experiences and increasing life satisfaction.